Peran Orang Tua untuk Meningkatkan Pengetahuan dan Sikap Remaja terhadap Pernikahan Usia Dini - Baiq Yuni Fitri Hamidiyanti; Intan Gumilang Pratiwi; Mutiara Rachmawati Suseno; Syajaratuddur Faiqah; Ati Sulianty (Poltekkes Kemenkes Palu, 2022)
Introduction: Factors causing early marriage in NTB include coercion from parents. For example, interviews with six young women who married early showed that two people married because of promiscuity, and two married because of coercion by their parents. One married because they liked each other, and one person had to get married, afraid of being a disgrace to the family and society because going home too late. Late night with his girlfriend. Objective: to analyze the effect of developing parental role models to increase adolescent knowledge and attitudes towards early marriage in West Lombok Regency. Method: quasi-experiment with pretest-posttest research design with Mann-Whitney test. The research location is in Sigerongan, West Lombok Regency, and carried out for three months with a population of male and female adolescents aged 15-19 years and a sample of 40 adolescents who were grouped into two groups. The sampling method used simple random sampling. Result: there is a significant difference in the value of knowledge between the intervention group and the control group. Conclusion: there is a significant difference between the intervention group and the control group, and there are differences in the post-test results of adolescent attitudes towards early marriage in the intervention group and the control group.